2000
DOI: 10.1177/135245850000600605
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction and extent of white matter abnormalities in multiple sclerosis: a clinical and MR study

Abstract: Our findings show, in MS patients with stable neurological impairment and no recent disease exacerbation, a correlation between smell loss and the lesion load in the regions of the brain involved in olfaction and support the theory that the extent and severity of MRI abnormalities in specific brain regions are related to the presence of selective neurologic and neuropsychologic impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 23 publications
6
55
0
Order By: Relevance
“…When analyzing the results, a patient with EDSS above 4 had 5.2 times the increased risk of olfactory alteration, which is consistent with other studies. Caminiti et al 7 and Silva et al 6 showed that olfactory dysfunction was correlated with higher EDSS scores, and a longer duration of disease, corroborating previous studies in which the olfactory dysfunction correlates directly to the level of disability 8,9,11,17 . Considering the relationship between the time of diagnosis and olfactory alteration, this study showed that patients with an abnormal test had a longer duration since diagnosis (p = 0.031), an average of 119 months, and that the older the patient, the greater the risk of olfactory alteration, as described by Silva et al 6 .…”
Section: Discussionsupporting
confidence: 75%
“…When analyzing the results, a patient with EDSS above 4 had 5.2 times the increased risk of olfactory alteration, which is consistent with other studies. Caminiti et al 7 and Silva et al 6 showed that olfactory dysfunction was correlated with higher EDSS scores, and a longer duration of disease, corroborating previous studies in which the olfactory dysfunction correlates directly to the level of disability 8,9,11,17 . Considering the relationship between the time of diagnosis and olfactory alteration, this study showed that patients with an abnormal test had a longer duration since diagnosis (p = 0.031), an average of 119 months, and that the older the patient, the greater the risk of olfactory alteration, as described by Silva et al 6 .…”
Section: Discussionsupporting
confidence: 75%
“…Some studies described a correlation between impaired olfactory function and the lesion load in cerebral MRI scans of MS patients [26,27]. A recent study concluded that olfactory T is impaired in early, active multiple sclerosis, whereas I is impaired in patients with longer disease duration and during the chronic phase of disease [28].…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the frequency of odour identification impairment was higher for patients with secondary progressive than relapsing-remitting or primary progressive courses [9]. Previous studies indicate that impaired olfactory function correlates with the lesion load in the olfactory brain [10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%